An injectable cell penetrable nano-polyplex hydrogel for localized siRNA delivery - Kim, Young-Min; Park, Mi-Ran; Song, Soo-Chang (ELSEVIER SCI LTD, 2013)
An approach for application of cell penetration to selective small interference RNA (siRNA) localized delivery system, cell penetrable nano-polyplex assembled hydrogel system, is presented. The cell penetrable nano-polyplex assembled hydrogelisprepared by protamine conjugation to poly(organophosphazene) and inducement of nano-polyplexes with siRNAs. After an injection of cell penetrable nano-polyplex solution into the body, it turns into a gel due to thermosensitivity of poly(organophosphazene). The gel maintains up to 4 weeks and the released 30 nm-sized nano-polyplexes from the gel induces highly effective siRNA delivery due to cell penetration. Accordingly, the new system shows a high gene silencing efficiency on only the target site in long-term with a single injection. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: RNA INTERFERENCE